Languages of Science in the Eighteenth Century - Gunnarsson, Britt-Louise (De Gruyter Mouton, 2011)
The eighteenth century is an important period both in the history of science and in the history of languages. In this volume, seventeen authors explore, from a variety of angles, the construction of a scientific language and discourse. The chapters explore the forming of scientific communities, the emergence of new languages of science, the spread of scientific ideas, and the development of scientific writing.